Secretion and Function of Salmonella SPI-2 Effector SseF Require Its Chaperone, SscB - Dai, Shipan (American Society for Microbiology, 2004)
Salmonella strains utilize a type III secretion system for their successful survival and replications inside host cells. SseF is one of the several effector proteins that are required for conferring this survival ability by altering the trafficking of the Salmonella-containing vacuoles. These effector proteins often require appropriate chaperones to maintain their stabilities inside the bacteria. These chaperones are also known to assist the subsequent secretion and translocation of their substrates. We report here that SscB acts as the chaperone for SseF, an effector for the Salmonella pathogenicity island 2 (SPI-2). We found that the sscB gene is required for the formation of Salmonella sp.-induced continuous filaments in epithelial cells. Efficient Salmonella replication in macrophages requires SscB function. Intracellular and secretion levels of SseF are greatly reduced in an sscB mutant strain compared to the wild-type strain. A protein stability assay demonstrated that the half-life of SseF is significantly shortened in the absence of SscB. Transcriptional analysis of the sseF gene showed that the effect of SscB on the SseF level is not at the transcriptional level. A coprecipitation experiment indicated that SscB interacts with SseF. In summary, our results indicate that SscB is a chaperone for SPI-2 effector SseF to facilitate its secretion and function inside the host cells.